2019
DOI: 10.1590/2179-8087.037818
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Planting Spacing In Production And Permeability Of Heartwood And Sapwood Of Eucalyptus Wood

Abstract: The objective of this work was to evaluate the influence of different useful areas provided by the planting spacings (3 × 1, 3 × 2, 3 × 3, 3 × 4 m) on the production and permeability of heartwood and sapwood of Eucalyptus grandis and Eucalyptus grandis × Eucalyptus urophylla clones at 4 years old. Regardless of the clone, there was no effect of planting spacing on the heartwood/sapwood relation and wood permeability. All clones showed a heartwood decrease with increased height, regardless of planting spacing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The presence of tyloses clogging the vessels is one of the reasons that reduce the permeability of the wood in the heartwood (De Micco et al 2016, Helmling et al 2018. Higher permeability values of Eucalyptus wood in the sapwood region are reported in the literature (Silva et al 2010, Brito et al 2019.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The presence of tyloses clogging the vessels is one of the reasons that reduce the permeability of the wood in the heartwood (De Micco et al 2016, Helmling et al 2018. Higher permeability values of Eucalyptus wood in the sapwood region are reported in the literature (Silva et al 2010, Brito et al 2019.…”
Section: Resultsmentioning
confidence: 98%
“…The mean basic density of Corymbia citriodora wood equal to 647 kg/m 3 (Table 1) is consistent with the literature, for example, Zanuncio et al (2015) found values between 665 and 684 kg/m 3 for Corymbia citriodora wood from seven-years-old trees, and Monteiro et al (2018) report mean values of basic density for trees of the same species and age equal to 610 kg/m 3 . The comparison with the values of water flow in wood is more complex since few studies approach the rates of the free and absorbed water in a detailed way, as well as diverse methodologies, are used for measure permeability, for example, apparatus for testing the permeability to air and liquid in wood (Silva et al 2010, Tanaka et al 2010, Baraúna et al 2014, Rezende et al 2018, Brito et al 2019 and gravimetric techniques (Redman et al 2016, Thybring et al 2018.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations